General geology and petrography of sedimentary rock at Kg. Keroh, Kuala Krai, Kelantan - Nur Syakirah Ikmal Hisham (2013)
A geological study which includes lithology, structural, texture, geomorphology, stratigraphy and petrography of sedimentary rock were studied at Kg. Keroh, Kuala Krai. The geological information at the study area was very limited. Therefore, this study was conducted to renew the geological information especially map. The rocks that have been found in the study area were andesite, sandstone, siltstone, shale and mudstone. While, petrographic study was conducted to identify the mineral presence and determine the origin of the rock. The study was carried out by means of field and laboratory works. The field works include the observation towards the lithology for each outcrop found, geomorphology and structural geology. While laboratory analyses were carried out using thin section, microscopy, and point counting. The percentage for each component presence within the sample was used to plot against the Pettijohn Diagram to determine the name of the rock. From the analysis, dominant mineral observed were plagioclase feldspar and quartz. There were also some of the components like cement, matrix, rock fragment and pore space. From the observation, the grain size and the shape of the grains were different. The composition of minerals was calculated and had showed different percentage. For sandstone, the grains sizes were large compared to siltstone, mudstone and shale and dominated by matrix. Therefore, the sandstone was classified as greywacke.